Living and other relics of pilgrims' Medjugorje - Belaj, Marijana (2013)
Medjugorje does not possess authentic, officially confirmed relics of the Virgin Mary. However, owing to the role and meanings attached to relics by pilgrims in general, and owing to the importance that relics have for pilgrimage sites, the author argues that the lack of “classic” relics in Marian Medjugorje has been substituted by living relics, i. e. by visionaries. Since the visionaries had or still have a direct contact with Mary, the pilgrims approach them as relics – consider them to be consecrated, as a living and accessible trace of Mary’s presence. Although the stress is placed on these living relics, the author will also point to some other relics, those related to the pilgrims’ concept of Medjugorje itself as a “holy ground”, to use a term of a pilgrim.
ENG